2020
DOI: 10.1080/0284186x.2020.1843190
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial determinants of adherence with oral anticancer treatment: ‘we don’t need no education’

Abstract: Introduction: Given the potentially fatal consequences of inadequate adherence with oral anticancer treatment in persons with cancer, understanding the determinants of adherence is vital. This paper aims at identifying psychosocial determinants of adherence to oral anticancer treatment. Methods: We reviewed the literature on psychosocial determinants of adherence with oral anticancer treatment, based on published literature in English, from 2015 to present. Literature searches were performed in PubMed, Embase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…We assessed the association between demographic, clinical, and psychosocial factors and adherence in the periods preceding and following the onset of the pandemic. Psychosocial factors included resilience, 10 coping styles, 11 illness perception 12 and self-efficacy, 13 which have been associated with adherence and visual function.…”
mentioning
confidence: 99%
“…We assessed the association between demographic, clinical, and psychosocial factors and adherence in the periods preceding and following the onset of the pandemic. Psychosocial factors included resilience, 10 coping styles, 11 illness perception 12 and self-efficacy, 13 which have been associated with adherence and visual function.…”
mentioning
confidence: 99%
“…However, medical record review of medication dosing may not equate to actual patient dosing because of medication adherence problems. 58 Third, our sample had a generally high level of education (59% reported college and postgraduate education). Thus, our results may be limited in generalizability to individuals with less formal education.…”
Section: Discussionmentioning
confidence: 87%
“…Second, the lack of medical record review as well as not taking into consideration any past or present neurologic history or medications that could affect self‐reported cognitive symptoms is a limitation. However, medical record review of medication dosing may not equate to actual patient dosing because of medication adherence problems 58 . Third, our sample had a generally high level of education (59% reported college and postgraduate education).…”
Section: Discussionmentioning
confidence: 97%
“…Robinson et al ( 2018 ), for example, reported that adherence to adjuvant endocrine therapy in women with breast cancer, a very important intervention method to reduce morbidity and mortality after a breast cancer diagnosis, diminished quite dramatically after a few years, implying the need to develop interventions that help increase this adherence. Systematic reviews and meta-analyses abundantly show that ‘providing information on the necessity to be adherent’ are almost completely missing their target in this population (Kaptein et al, 2021 ). Nevertheless, the mantra in almost all studies in this area is, ‘this study offers support for the need to develop interventions such as reminder letters or telephone calls to enhance persistence rates, especially when patients reach the later years of adjuvant endocrine therapy’ (Robinson et al, p. e14).…”
Section: Behaviour As the Central Outcome In Health Care (Kaplan ...mentioning
confidence: 99%
“…See also the study by Jansen et al ( 2013 ) where illness perceptions and treatment beliefs of people on hemodialysis were challenged and changed and brought in alignment with current nephrological expertise) . In an attempt to mock this view, the subtitle, ‘We don’t need no education’ was added to a paper on adherence to targeted therapy ( Figure 3 ; Kaptein et al, 2021 ). The Editor of the journal deserves praise for her decision to leave that subtitle untouched.…”
Section: Behaviour As the Central Outcome In Health Care (Kaplan ...mentioning
confidence: 99%